The great Gatsby : the graphic novel - Fordham, Fred, 1985-; Fordham, Fred, 1985-; Fitzgerald, F. Scott (Francis Scott), 1896-1940 (Scribner, 2020)
Jay Gatsby had once loved beautiful, spoiled Daisy Buchanan, then lost her to a rich boy. Now, mysteriously wealthy, he is ready to risk everything to woo her back. This is the definitive, textually accurate edition of a classic of twentieth-century literature, The Great Gatsby. The story of the fabulously wealthy Jay Gatsby and his love for the beautiful Daisy Buchanan has been acclaimed by generations of readers; however the first edition contained a number of errors resulting from Fitzgerald's extensive revisions and a rushed production schedule.